The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2004
DOI: 10.1111/j.1399-6576.2004.00504.x
|View full text |Cite
|
Sign up to set email alerts
|

Low‐dose bupivacaine with sufentanil prevents hypotension after spinal anesthesia for hip repair in elderly patients

Abstract: A reduced dose of hyperbaric bupivacaine (7.5 mg) in combination with sufentanil (5 microg) provides reliable spinal anesthesia for the repair of hip fracture in aged patients with few events of hypotension and little need for vasopressor support of blood pressure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
74
3
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 77 publications
(91 citation statements)
references
References 21 publications
10
74
3
1
Order By: Relevance
“…These findings are consistent with the results of Asehnoune et al 13 No significant difference (P>0.05) between the mean respiratory rate in both the groups throughout the observation period. There was no respiratory depression in any of the patients of either group that was similar to studies of Olofsson et al 8 Nausea and vomiting was seen only in patients of group B. No clinically significant sedation occurred in any of the patients of either group.…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…These findings are consistent with the results of Asehnoune et al 13 No significant difference (P>0.05) between the mean respiratory rate in both the groups throughout the observation period. There was no respiratory depression in any of the patients of either group that was similar to studies of Olofsson et al 8 Nausea and vomiting was seen only in patients of group B. No clinically significant sedation occurred in any of the patients of either group.…”
Section: Discussionsupporting
confidence: 71%
“…These findings of the present study are similar to results of Ben David et al Olofsson et al also found that there was statistically significant decrease in degree and duration of motor block when 7.5 mg of bupivacaine with 5 mg sufentanil was compared with 15 mg of bupivacaine. 8 From the studies of Sundnes et al and Axelsson et al we can conclude that by reducing the dose of local anesthetic, the cephalad spread, degree of motor block and duration of motor block can be decreased. 9,10 The addition of sufentanil enhances the somatic analgesia thus achieving similar peak sensory levels with smaller dose of local anaesthetic thus induction to baby delivery time can be reduced.…”
Section: Discussionmentioning
confidence: 99%
“…precipitate heart failure. To minimize such risks, and to decrease the incidence of hemodynamic instability in high risk surgical populations (the elderly, patients with ischemic heart disease and/or a history of heart failure), it has been suggested that the dose of LAAs be reduced by combining LAAs with adjuvant drugs such as sufentanil 40 or to administer LAAs continuously via spinal anesthesia. 41 The following points must be considered in the assessment of the clinical relevance of our results.…”
Section: +mentioning
confidence: 99%
“…This include lignocaine, bupivacaine, alfentanyl, sufentanyl, butorphanol, fentanyl etc. [6][7][8] It was observed that in our hospital we use lignocaine for spinal anesthesia since many years without any major complications. We found that studies mentioned in literature comparing use of local anesthetic for spinal anesthesia have small sample size of patients.…”
Section: Introductionmentioning
confidence: 99%